Identification of damage and assessment of the jetty using Non destructive method (NDT) - Efendi, Aco Wahyudi (Dinamika Bahari, 2025)
A pier is a port building used for anchoring and mooring ships carrying out loading and unloading of goods and loading and unloading of passengers. This research was conducted to obtain information about the feasibility of a jetty. From the visual results of the dive team's survey, it shows that corrosion occurs from the surface of the high tide to the surface of the riverbed, this can be seen from some of the documentation that there is a porous surface of steel pipe piles. In steel pipe, 56.25% (thickness less than 12 mm) of the 16 piles indicated that they were porous and loose which, in the reduction of the thickness of the steel pipe. About 43.75% (thickness more than 12 mm) is weathered so that its dimensions have increased in thickness of steel pipe dimensions. For pile integrity, the results obtained are 33.34% pile integrity less than 60% from 15 test points, 33.34% integrity from 60-79% from 15 test points, 6.67% integrity from 80-99% from 15 test points, 20% of the 15 test points failed. The current condition of the wharf is weakened due to natural conditions as well as due to age and service load, therefore a decrease in capacity affects the behavior of the pier so that the collision that occurs causes a very high vibration cycle.